Metabolites in the association between early-life famine exposure and type 2 diabetes in adulthood over a 5-year follow-up period - Wen Zhang; Ningjian Wang; Yingli Lu; Chi Chen; Fangzhen Xia; Yuying Wang; Heng Wan (BMJ Open Diabetes Research & Care)
Introduction Exposure to malnutrition in early life has been found to significantly elevate type 2 diabetes risk in adulthood. However, the changes in metabolites resulting from malnutrition in early life have not been studied. The aim of this study was to identify metabolites with levels associated with type 2 diabetes resulting from exposure to China’s Great Famine (1959–1962).Research design and methods Participants were from SPECT-China 2014 and SPECT-China2 2019, two cross-sectional studies performed at the same site. In total, 2171 subjects participated in SPECT-China and SPECT-China2 simultaneously. The sample size of fetal-exposed (1959–1962) versus non-exposed (1963–1974) individuals was 82 vs 79 in 2014 and 97 vs 94 in 2019. Metabolomic profiling was performed between famine-exposed and non-exposed groups.Results Among the different famine exposure groups, the fetal-exposed group (1959–1962) had the greatest incidence rate (12.5%), with an OR of 2.11 (95% CI 1.01 to 4.44), compared with the non-exposed group (1963–1974). Moreover, compared with those in the non-exposed group (1963–1974), four metabolites (indole-3-carbinol (I3C), phosphatidylcholine (PC) (22:6(4Z,7Z,10Z,13Z,16Z,19Z)/16:1(9Z)), pyrimidine, and PC(16:1(9Z)/22:5(4Z,7Z,10Z,13Z,16Z))) showed significantly lower relative intensities in the famine and diabetes groups both in 2014 and 2019. Pyrimidine significantly mediated the association of famine exposure with diabetes, and I3C marginally mediated this association.Conclusions Famine exposure in the fetal period could increase type 2 diabetes risk in adults, even those in their 60s. I3C and pyrimidine are potential mediators of the effects of famine exposure on diabetes development.